2013
DOI: 10.1152/jn.01096.2012
|View full text |Cite
|
Sign up to set email alerts
|

Fixational saccades reflect volitional action preparation

Abstract: Human volitional actions are preceded by preparatory processes, a critical mental process of cognitive control for future behavior. Volitional action preparation is regulated by large-scale neural circuits including the cerebral cortex and the basal ganglia. Because volitional action preparation is a covert process, the network dynamics of such neural circuits have been examined by neuroimaging and recording event-related potentials. Here, we examined whether such covert processes can be measured by the overt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 76 publications
(128 reference statements)
9
48
0
1
Order By: Relevance
“…As the preparatory sensory acquisition before movement offers substantial evolutionary advantages, it may be a general feature of the vertebrate brain. Recent studies in humans found a link between preparatory visual sampling and voluntary eye movements, by measuring fixational saccades occurring before the stimulus appearance that signalled voluntary gaze (Watanabe et al, 2013). A sustained period of heightened sensory sampling during movement preparation could improve the detectability of weak or infrequent sensory signals in a noisy background that might be biologically important (Ratnam and Nelson, 2000;Gussin et al, 2007).…”
Section: Functional Significance Of Preparatory Sensory Acquisition Amentioning
confidence: 99%
“…As the preparatory sensory acquisition before movement offers substantial evolutionary advantages, it may be a general feature of the vertebrate brain. Recent studies in humans found a link between preparatory visual sampling and voluntary eye movements, by measuring fixational saccades occurring before the stimulus appearance that signalled voluntary gaze (Watanabe et al, 2013). A sustained period of heightened sensory sampling during movement preparation could improve the detectability of weak or infrequent sensory signals in a noisy background that might be biologically important (Ratnam and Nelson, 2000;Gussin et al, 2007).…”
Section: Functional Significance Of Preparatory Sensory Acquisition Amentioning
confidence: 99%
“…Neural activity for saccade preparation builds up over time (Dorris, Pare, & Munoz, ; Everling & Munoz, ; Watanabe & Munoz, ), which could be readout by fixational eye movements (Jainta et al., ; Wang et al., ; Watanabe et al., ). We therefore included the following two conditions that manipulated fixation durations to modulate saccade preparation experimentally; random and constant conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Volitional action preparation can be defined operationally as neural processes controlling the preparatory activity across the neural axis (Haggard, ). We hypothesized that such processes could possibly be readout by fixational eye movements because modulations in the frequency of fixational saccades and pupil dilation are in accordance with neural signals controlling volitional saccades during the antisaccade paradigm (Wang et al., ; Watanabe et al., ).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations